Harmony in Leadership: Analyzing Successful Relationship Dynamics in Yogyakarta-Kyoto's Sister Province Collaboration - Gunawan, Tedi (Nation State: Journal of International Studies, 2023)
In an era where globalization is reshaping every facet of our lives, international cooperation holds the key to progress. The Special Province of Yogyakarta seized the moment to forge a transformative partnership with Japan's Kyoto Prefecture, inaugurated on 16th July 1985. This study delves into the tapestry of this 'sister province' cooperation, tracing its historical trajectory and discerning the elements behind its enduring success. Employing qualitative research involving stakeholders’ interviews from both regions, this study unveils compelling insights. This cooperation emerges as successful model of 'sister province' initiatives in Indonesia, aligning seamlessly with the government's benchmarks—ranging from mutual benefits and sustainable initiatives to positive community impacts. It is also found that leadership factors influence the success of this sister province cooperation. Both leaders can manage and encourage collective action to support this cooperation. Moreover, both regions boast a vibrant cultural heritage, sharing numerous similarities that energize and deepen the ties between these sister provinces. Yet, even amidst its achievements, challenges like budgetary constraints and manpower shortages cast shadows. This research, therefore, not only unveils the success story of the Yogyakarta-Kyoto cooperation, but also enriches scholarly discussion on the broader contributions of 'sister province' initiatives in Indonesia international cooperation landscape.